Analisis Pengelolaan Sedekah Sistem Kencleng untuk Kemaslahatan Siswa MI Kalifa Nusantara (Studi Kasus BAZNAS Kota Denpasar) - Printaro, Edo Gutsy; Kurniawati, Kurniawati; Iswahyuni, Iswahyuni (Maisyatuna, 2023)
Almsgiving is a form of love for Allah blessings that have been given to him, so that a servant is willing to set aside a portion of his assets for religious purposes, both in the context of helping others and the struggle for Islamic da'wah. In line with that BAZNAS Denpasar City has implemented a kencleng system alms program which aims to educate students to learn alms from an early age through the management of BAZNAS Denpasar City which synergizes with Muslim schools in Denpasar City, one of which is MI Kalifa Nusantara. The research objectives were to determine: 1) Management of alms kencleng system at MI Kalifa Nusantara in BAZNAS Denpasar City. 2) The benefit of the kencleng system in MI Kalifa Nusantara. This research method is descriptive-qualitative. The informants were 10 people who were selected purposively. Collecting data based on facts and data through observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. Based on the results of the research, the management of the kencleng alms system by BAZNAS Denpasar City which is based on Islamic law, trust, benefit, justice, legal certainty, integration, and accountability can provide benefits for MI Kalifa Nusantara students which include religion, soul, mind, descent and property. With this system, students can start learning alms from an early age and at the same time help their underprivileged friends in their education through the guidance of teachers and through the continuous program of BAZNAS Denpasar City.